Narrativas Públicas e Constitucionalismo na Abdicação de D. Pedro I em 1831 (Ágora Journal, 2021)
At a time of intense political disputes over the organization of the constitutional order at the end of the reign of Pedro I, the narratives, which can be understood as stories that mixed rumors, facts and emotions, were widely disseminated in the public sphere. We analyze in this text to what extent and in what way those narratives - the recolonization of Brazil and the stories about a supposed anti-nationalism of the Emperor - generated behaviors that contributed to Abdication. Based on analytical references on the dissemination of narratives and rumors, we conclude that the narratives stimulated behaviors that self-confirmed them and thus amplified their effects, contributing to bring together groups with diverse demands around a common cause, which contributed to delegitimize the figure of the emperor.